Advances in research on classroom dialogue: Commentary on the articles. (April 2017) - Howe, Christine
Abstract: This commentary reviews the six articles that comprise the Special Issue on 'Advances in research on classroom dialogue: Learning outcomes and assessments'. The commentary focuses on the general methodological and conceptual messages that can be drawn from the reported research and that are relevant for progressing the field further. Issues discussed include the conceptualization and assessment of oral communicative competence; the meaning of 'participation' within the context of dialogue and the implications of participation for student outcomes; and the characterization of educationally productive dialogue. The commentary concludes by anticipating research that does not merely specify the productive features but also elucidates the processes by which the features have their positive effects. Highlights: Discussion of issues relating to the conceptualization and assessment of oral communicative competence. Analysis of the meaning of 'participation in dialogue' and the implications of participation for student outcomes. Concrete suggestions (in terms of methods and concepts) for future progress.